Design principles for intertwining local and nonlocal mathematics - The case of relating registers and representations in Abstract Algebra - Dellori, Anna; Wessel, Lena (Proceedings of INDRUM2022 (International Network for Didactic Research in University Mathematics)

Rational Defeasible Subsumption in DLs with Nested Quantifiers: the Case of ELI\(\perp\) - de Camargo e Souza Câmara, Igor; Turhan, Anni-Yasmin (Proceedings of the 20th International Workshop on Non-Monotonic Reasoning, NMR 2022, Part of the Federated Logic Conference (FLoC 2022), Haifa, Israel, August 7-9, 2022)

Rules and Reasoning - 6th International Joint Conference on Rules and Reasoning, RuleML+RR 2022, Berlin, Germany, September 26-28, 2022, Proceedings

Pre-service Teachers' Professional Development: Relating Abstract Algebra and School Algebra - Dellori, Anna; Wessel, Lena (Proceedings of the 24th Annual Conference on Research in Undergraduate Mathematics Education)

Investigation of the combustion chemistry in laminar, low-pressure oxymethylene ether flames (OME0–4) - Gaiser, Nina; Zhang, Hao; Bierkandt, Thomas; Schmitt, Steffen; Zinsmeister, Julia; Kathrotia, Trupti; Hemberger, Patrick; Shaqiri, Shkelqim; Kasper, Tina; Aigner, Manfred; Oßwald, Patrick; Köhler, Markus (Combustion and Flame)
Quantitative speciation data for alternative fuels is highly desired to assess their emission potential and to develop and validate chemical kinetic models. In terms of substitute choices for fossil diesel are oxymethylene ethers (OMEs) strongly discussed. Due to the absence of carbon-carbon bonds, soot emis-sions from combustion of OMEs are low, but significant emissions of unregulated pollutants such as alde-hydes emerge. The combustion behavior of OME fuels with different chain lengths, OME0-4, was investigated in lam-inar premixed low-pressure flames using complementary molecular-beam mass spectrometry (MBMS) techniques. MBMS sampling provides an in-situ access directly into the reaction zone of the flame. Al-most all chemical species involved in the oxidation process can be detected and quantified simultane-ously. Neat OME0-3 flames were analyzed by electron ionization (EI) MBMS with high mass resolution ( R approximate to 3900) providing exact elementary composition. To obtain isomer-specific information, an OME1- doped hydrogen flame and a stochiometric OME4 flame were studied by double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy. Both, EI-MBMS detection and i2PEPICO spectroscopy, en-ables a complete overview of all intermediates. The results show a dominance of oxygenated intermediates for all measured conditions. Mole fraction profiles for the most important species are presented (i.e. formaldehyde, methanol, methyl formate and formic acid) and compared to modeling results. Hydrocarbons with more than four carbon atoms were not detected under the investigated conditions. Isomers such as ethanol/dimethyl ether (m/z = 46) and ethenol/acetaldehyde (m/z = 44) could be separated using threshold photoelectron spectra for clear iden-tification and photoionization efficiency curves for quantification. This investigation permits the discus-sion and analysis of systematic trends, including intermediate species, for the combustion of the studied series of oxymethylene ether fuels. (c) 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

On the diversity of fossil and alternative gasoline combustion chemistry: A comparative flow reactor study - Zinsmeister, Julia; Gaiser, Nina; Melder, Jens; Bierkandt, Thomas; Hemberger, Patrick; Kasper, Tina; Aigner, Manfred; Köhler, Markus; Oßwald, Patrick (Combustion and Flame)
Recent progress in molecular combustion chemistry allows for detailed investigation of the intermediate species pool even for complex chemical fuel compositions, as occur for technical fuels. This study pro-vides detailed investigation of a comprehensive set of complex alternative gasoline fuels obtained from laminar flow reactors equipped with molecular-beam sampling techniques for observation of the com-bustion intermediate species pool in homogeneous gas phase reactions. The combination of ionization techniques including double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy enables deeper mechanistic insights into the underlying reaction network relevant to technical fuels. The se-lected fuels focus on contemporary automotive engine application as drop-in fuels compliant to European EN 228 specification for gasoline. Therefore, potential alternative gasoline blends containing oxygenated hydrocarbons as octane improvers obtainable from bio-technological production routes, e.g., ethanol, iso- butanol, methyl tert -butyl ether (MTBE), and ethyl tert -butyl ether (ETBE), as well as a Fischer-Tropsch surrogate were investigated. The fuel set is completed by two synthetic naphtha fractions obtained from Fischer-Tropsch and methanol-to-gasoline processes alongside with a fossil reference gasoline. In total, speciation data for 11 technical fuels from two atmospheric flow reactor setups are presented. Detailed main and intermediate species profiles are provided for slightly rich ( 4) = 1.2) and lean ( 4) = 0.8) con-ditions for intermediate to high temperatures. Complementary, the isomer distribution on different mass channels, like m/z = 78 u fulvene/benzene, of four gasolines was investigated. Experimental findings are analyzed in terms of the detailed fuel composition and literature findings for molecular combustion chemistry. Influences of oxygenated fuel components as well as composition of the hydrocarbon frac-tions are examined with a particular focus on the soot precursor chemistry. This dataset is available for validation of chemical kinetic mechanisms for realistic gasolines containing oxygenated hydrocarbons.(c) 2021 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Ein kritisch-multiperspektivischer Blick auf Forschendes Lernen in der Lehrkräftebildung - Bloh, Thiemo; Caruso, Carina (die hochschullehre)
Forschendes Lernen in der Lehrer:innenbildung ist seit der Ausweitung schulpraktischer Anteile bzw. der Einführung des sogenannten Praxissemesters eng verwoben mit der Lehrer:innenausbildung. Gleichzeitig wird bisher weitestgehend different beantwortet, was Forschendes Lernen ist und sein kann sowie warum es wie hochschuldidaktisch gerahmt wird und werden sollte. Der Beitrag widmet sich dieser Frage. Dabei zeigt sich einerseits, dass hochschuldidaktische Zugänge zur Realisierung Forschenden Lernens in der Lehrer:innenbildung erst vor dem Hintergrund theoretischer Annahmen zur Entwicklung von Lehrpersonen und deren Professionalität sowie zur Gestalt - gemeint ist hier der Beitrag zu dieser Entwicklung sowie der Anteil an Professionalität - Forschenden Lernens entwickelt werden können, eine solche Fundierung aber oftmals ausbleibt. Andererseits wird herausgearbeitet, inwiefern eine Differenz zwischen wissenschaftlicher Forschung und Forschung im Forschenden Lernen besteht. Daran anschließend wird eine habitustheoretische Fundierung Forschenden Lernens vorgestellt und es werden exemplarisch deren Implikationen für die Gestaltung Forschenden Lernens benannt. Abschließend wird anhand empirischer Rekonstruktionen beispielhaft eine praktische Umsetzung diskutiert.
Keywords: Forschendes Lernen; Lehrer:innenausbildung; Praxissemester; Professionalisierung / Research-based learning; teacher education; internships; professionalization

Insights into the decomposition of zirconium acetylacetonate using synchrotron radiation: Routes to the formation of volatile Zr-intermediates - Grimm, Sebastian; Baik, Seung-Jin; Hemberger, Patrick; Kasper, Tina; Kempf, Andreas M.; Atakan, Burak (Journal of Materials Research)
Abstract The thermal decomposition of Zr(acac) 4 is studied in a SiC-microreactor on the micro-second time scale. By utilizing synchrotron radiation and photoelectron photoion coincidence spectroscopy, six important zirconium intermediates, as for instance Zr(C 5 H 7 O 2 ) 2 (C 5 H 6 O 2 ), and Zr(C 5 H 6 O 2 ) 2 , are identified in the gas phase for the first time. The adiabatic ionization thresholds of intermediately formed zirconium species are estimated and the main products of their thermal decomposition, acetylacetone, acetylallene and acetone are characterized unambiguously and isomer-selectively. Based on all detected intermediates, we deduce the predominant pyrolysis pathways of the precursor in the temperature range from 400 to 900 K. Our findings are complemented by numerical simulations of the flow field in the microreactor, which show that the choice of dilution gas significantly influences the temperature profile and residence times in the microreactor, such that helium provides a more uniform flow field than argon and should preferentially be used. Graphical abstract Using a soft ionization method coupled to velocity map imaging (VMI), leads to valuable insights in the thermal decomposition of Zr(C 5 H 7 O 2 ) 4 , used in the synthesis of functional nanomaterials and ceramic coatings. Thanks to the use of a microreactor, important gas
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mechanism and Kinetics of the Thermal Decomposition of Fe(C5H5)2 in Inert and Reductive Atmosphere: A Synchrotron‐Assisted Investigation in A Microreactor - Grimm, Sebastian; Hemberger, Patrick; Kasper, Tina; Atakan, Burak (Advanced Materials Interfaces)
Abstract The decomposition and reduction of ferrocene, an important precursor for iron chemical vapor deposition and catalyst for nanotube synthesis, is investigated in the gas‐phase. Reactive intermediates are detected to understand the underlying chemistry by using a microreactor coupled to a synchrotron light source. Utilizing soft photoionization coupled with photoelectron‐photoion coincidence detection enables us to characterize exclusive intermediates isomer‐selectively. A reaction mechanism for the ferrocene decomposition is proposed, which proceeds as a two‐step process. Initially, the molecule decomposes in a homogeneous surface reaction at temperatures <900 K, leading to products such as cyclopentadiene and cyclopentadienyl radicals that are immediately released to the gas‐phase. At higher temperatures, ferrocene rapidly decomposes in the gas‐phase, losing two cyclopentadienyl radicals in conjunction with iron. The addition of hydrogen to the reaction mixture reduces the decomposition temperature, and changes the branching ratio of the products. This change is mainly attributed to the H‐addition of cyclopentadienyl radicals on the surface, which leads to a release of cyclopentadiene into the gas‐phase. On the surface, ligand fragments may also undergo a series of catalytic H‐losses leading most probably to a high carbon content in the film. Finally, Arrhenius parameters for both global reactions are presented.
Keywords: Mechanical Engineering; Mechanics of Materials

Jupyter Notebooks for Teaching, Learning, and Doing Data Science - Fleischer, Yannik; Hüsing, Sven; Biehler, Rolf; Podworny, Susanne; Schulte, Carsten (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
We report on our work with students in our data science courses, focusing on the analysis of students’ results. This study represents an in-depth analysis of students’ creation and documentation of machine learning models. The students were supported by educationally designed Jupyter Notebooks, which are used as worked examples. Using the worked example, students document their results in a so-called computational essay. We examine which aspects of creating computational essays are difficult for students to find out how worked examples should be designed to support students without being too prescriptive. We analyze the computational essays produced by students and draw consequences for redesigning our worked example.

Model-based design of a segmented reactor for the flexible operation of the methanation of CO2 - Herrmann, Felix; Grünewald, Marcus; Riese, Julia (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Demand Side Management in Biogas Plants - Dynamic Simulation of the Influence of Time-varying Agitation on Biogas Production - Lilli, Lilli; Röder, Lilli; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Energy Proceedings)

"Schwangerschaft ressourcenorientiert erleben" (SRE-Studie) - Das Zürcher Ressourcen Modell (ZRM) als Intervention zur Stressreduktion in der Geburtsvorbereitung. - Schneider, Tamara; Weber, Julia; Bauer, Nicola H.

"ProGRess" - Prokrastination reduzieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

"Schwangerschaft ressourcenorientiert erleben" (SRE-Studie) - Stressreduktion in der Schwangerschaft mit dem Zürcher Ressourcen Modell (ZRM). - Schneider, Tamara; Weber, Julia; Bauer, Nicola H.

"ProGRess" - Prokrastination ressourcenstark und gesundheitsfördernd begegnen. - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Ressourcen gegen Prokrastination aktivieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

Mixed-Signal Baseband Circuit Design for High Data Rate Wireless Communication in Bulk CMOS and SiGe BiCMOS Technologies - Javed, A. R.

Rahmenwerk zur Gestaltung des Technologietransfers in mittelständisch geprägten Innovationsclustern - Fechtelpeter, Christian

Inklusion und Sprachbildung: „Das habe ich noch nie vorher versucht, also bin ich völlig sicher, dass ich es schaffe“ : Eine interdisziplinäre Perspektive auf den Geschichtsunterricht - Altun, Tülay; Günther, Katrin; Markus, Bernhardt (Fachorientierte Sprachbildung und sprachliche Vielfalt in der Lehrkräftebildung: Hochschuldidaktische Formate an der Universität Duisburg-Essen)